Análisis dinámico incremental de puentes con diferentes tipos de apoyo - Alcalá Ferreira, Andrea (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
This thesis aims to assess the behavior of continuous box girder bridges, when different types of seismic isolation and energy dissipation systems are used, considering the effect of the transverse seismic shear keys and deck‐abutment pounding interaction that occurs when the closing girder movement at an expansion joint is greater than the joint gap. The evaluation was developed by means of nonlinear dynamic analyses of eight different models with the earthquake acting in the transverse direction and seven models with the earthquake acting in the longitudinal direction. In accordance with the performance‐based design philosophy, it is important to estimate the behavior and damage level of structures, for different seismic intensity levels. For this reason, the study is performed by incremental dynamic analyses, which evaluate the response that range from the stage of elastic behavior, up to the failure of the system. Non‐linear behavior due to damage of the elements was concentrated on the upper and lower ends of the piers. In addition, it was considered the contact nonlinear behavior due to the interaction of the superstructure with the seismic shear keys and abutments. The dynamic curves for increasing levels of seismic intensity and corresponding damage measures were obtained for different seismic records. The occurrence of the following four damage limit states is identified: Cracking, onset of spalling, extended spalling and collapse. In addition, deformations of the deck, drift ratio of the piers and shear deformation of neoprene bearings were obtained.

En este trabajo se evalúa el comportamiento de puentes continuos de sección cajón, cuando se utilizan distintos tipos de aisladores y disipadores de energía sísmica, considerando el efecto de los topes sísmicos transversales y el choque del tablero con los estribos cuando se cierran las juntas de dilatación. Para ello se llevó a cabo el análisis dinámico no lineal de ocho modelos diferentes cuando el sismo actúa en la dirección transversal y siete modelos con el sismo actuando en la dirección longitudinal. Conforme con la filosofía de diseño por desempeño, es necesario conocer el comportamiento y nivel de daño de las estructuras para distintos niveles de intensidad sísmica. Por tal motivo, el estudio se realiza mediante un análisis dinámico incremental, con el que se evalúa la respuesta desde la etapa de comportamiento elástico, hasta la falla del sistema. El comportamiento no lineal debido al daño de los elementos se concentró en los extremos superior e inferior de las pilas. Adicionalmente se consideró el comportamiento no lineal de contacto debido a la interacción de la superestructura con los topes sísmicos y con los estribos. Con los análisis se obtuvieron curvas de capacidad dinámica para distintas medidas de intensidad y demanda. Se identificaron cuatro niveles de daño: fluencia, pérdida de recubrimiento, propagación de la pérdida de recubrimiento y colapso. Se aplicaron distintos registros sísmicos naturales que fueron escalados para producir cada uno de los niveles de daño. Adicionalmente, se obtuvieron las deformaciones del tablero, las distorsiones de las pilas y por último las distorsiones de los apoyos.
Facultad de Ingeniería Civil. Maestría en Ingeniería en el Área de Estructuras
Keywords: info:eu-repo/classification/cti/7; FIC-M-2017-1164; Análisis dinámico incremental; Aisladores y disipadores; Balanceo de la cimentación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4076